Analisis Akuntansi Manajemen Sektor Publik Di Kantor Desa Sei Rotan - Aisyah Fadilah Lubis; Putri Kumala Dewi Lubis; Indriana Dachi; Rina Rina (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2024)
Public sector management accounting is a system that provides accountability information and management control for the government and society. This system serves as an information tool that provides transparent, accurate, and accountable financial reports, so that the public can understand the use of public funds and increase trust in this Sei Rattan Village Office.In public sector management accounting, transparent and accurate public financial reports are used as the main instrument for creating public accountability. These reports are used in the management control process, from strategic planning to performance reporting. In addition, public sector management accounting also functions as a supervisory tool carried out by internal parties at the Sei Rotan Village Office in an open and continuous manner. Thus, public sector management accounting has an important role in increasing transparency and accountability at the Sei Rotan Village Office, as well as increasing public trust in the Sei Rotan Village Office. Therefore, the active role of the Sei Rotan Village Office and the community in increasing the use of transparent and accurate financial reports is needed to increase transparency and accountability in the public sector.